2015
DOI: 10.1007/s11523-015-0394-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of Monotherapy with KHK2866, an Anti-Heparin-Binding Epidermal Growth Factor-Like Growth Factor Monoclonal Antibody, in Patients with Advanced Cancer

Abstract: The study was terminated because of neuropsychiatric toxicity. The only predictive factor for neuropsychiatric toxicity was administration of KHK2866. These effects were reversible, but were not predictable. Their etiology is not presently understood. [Study registered at ClinicalTrials.gov #NCT0179291].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Targeting of HB-EGF has been aimed to inhibit growth and metastasis of various cancers [ 36 , 63 72 ]. Diverse approaches for HB-EGF targeting have been tested including blocking antibodies [ 63 , 65 , 66 , 70 ] and inert diphtheria toxin derivatives [ 71 , 73 ]. Unexpectedly, the HB-EGF blocking antibodies caused neurological side effects, which caused discontinuation of human trial [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting of HB-EGF has been aimed to inhibit growth and metastasis of various cancers [ 36 , 63 72 ]. Diverse approaches for HB-EGF targeting have been tested including blocking antibodies [ 63 , 65 , 66 , 70 ] and inert diphtheria toxin derivatives [ 71 , 73 ]. Unexpectedly, the HB-EGF blocking antibodies caused neurological side effects, which caused discontinuation of human trial [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse approaches for HB-EGF targeting have been tested including blocking antibodies [ 63 , 65 , 66 , 70 ] and inert diphtheria toxin derivatives [ 71 , 73 ]. Unexpectedly, the HB-EGF blocking antibodies caused neurological side effects, which caused discontinuation of human trial [ 70 ]. Similar neurological effect was also shown in mice with brain-specific HB-EGF knockout [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…HB-EGF-targeted agents have been tested in two phase I clinical trials, which investigated the safety, tolerability, and efficacy of the inhibitory monoclonal antibody to HB- EGF KHK2866 in patients with advanced ovarian cancer and of BK-UM in patients with recurrent ovarian cancer (21,23). Companion diagnostics for each agent were also developed (8,24).…”
Section: Discussionmentioning
confidence: 99%
“…Companion diagnostics for each agent were also developed (8,24). The studies found that serum HB-EGF levels were reduced by intravenous injection of KHK2866 (23), and significantly reduced by intraperitoneal administration of BK-UM in patients with high levels of serum HB-EGF (>125 pg/ml by ELISA) (21). However, the KHK2866 antibody caused reversible neuropsychiatric toxicity and its development has been discontinued (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation